EFL students' perceptions towards Quizizz usage in English subject formative assessment - Aisyah Bindiya; Niko Fediyanto (Universitas Islam Malang, 2023)
Currently, developing technology encourages English teachers to be able to use several educational platforms. Quizizz is one of the educational innovations carried out to achieve learning goals. This study uses a qualitative descriptive research method. In this research, the focus is on exploring how students perceive Quizizz, a formative assessment tool rooted in the Unified Theory of Acceptance and Use of Technology (UTAUT). The study adapts and customizes an interview guide from prior research and investigates four aspects: performance expectations, effort expectations, social influence, and facilitating conditions. Researchers conducted research at SMK Sumber Ilmu Tulangan, using Quizizz as a formative assessment tool in English lessons. Data collection included semi-structured interviews and documentation showing positive responses to performance expectations, effort expectations, social influence, and facilitating conditions. However, concerns were raised regarding the limitations of question types, signal problems, and the lack of school-provided facilities.